The Science of Knowledge in Islam: An Anthropological Perspective - Bothwell, Mustafa (The Journal of Rotterdam Islamic and Social Sciences, 2015)
In the last decade and a half, anthropologists have devoted increased attention to the practice and perception of science. Many scholars of anthropology point to science as one of three broad areas of opportunities for anthropological study. These scholars also claim that anthropological studies of science will lead to important discoveries about our contemporary world while helping anthropologists bridge their own internal differences. The emergence of the anthropology of science occurred simultaneously with the rise of science and technology studies (STS). Science and technology studies (STS), which is dominated by the Western-oriented disciplines of history, philosophy, and sociology, has focused almost exclusively on Euro-American science. The researchers have ignored the majority of socio-cultural contexts in which science is practiced. This study will improve knowledge of the practice and perception of science outside the Euro-American context, the Islamization of knowledge debate. The examination of the intersection of the "local" and "global" context of knowledge production is central to this study. This study identifies two major strands of research in the anthropology of science, namely, cultures of science and science of cultures. Substantive contributions of researchers studying cultures of science include greater understandings of the processual nature of knowledge formation and experimentation, the social structure of laboratories, internal scientific communication, and the production of scientific texts. Studies of science and culture examine the ways that science transcends its traditional settings like laboratories and becomes embedded in society. This study attempts to describe the history and philosophical underpinnings of the contemporary Islamization of knowledge debate. It will argue that Muslim intellectuals engaged in the Islamization of knowledge advocate one of the three distinct philosophical positions which can be labeled the modernization, indigenization, and nativization approaches. After a discussion of similar debates during the late nineteenth and early twentieth centuries, the study will then describe these three approaches in terms of their philosophies, legitimation strategies, and political implications before concluding.